Real-Time Monitoring System for Thermocouple Inhomogeneity Equipment. Issue 1 (1st June 2022) - Nugraha, H; Imaduddin, A; Achmadi, A; Suryadi; Wismogroho, A S
Abstract: Thermocouple inhomogeneity equipment was developed to measure the Seebeck coefficient characteristic in each wire position based on the effect of temperature exposure along the thermocouple wire. Temperature and distance sensors are used to measure the temperature output of the heating system and the movement of the thermocouple position. We developed a real-time measurement system to monitor the measurement of the thermocouple sensor based on a microcontroller. This monitoring system is needed to monitor changes in the ice bath during measurement, if the ice bath was unstable or being melting, it can affect the output voltage of the thermocouple. The program was compiled and uploaded to ESP 32 then monitoring data with an open-source internet of things called Thingspeak was used as a platform to retrieve and display the collected data. Real-time monitoring of distance from ultrasonic and temperature of heat source (heat gun) can be accessed through web applications and smartphones. The data were analyzed based on conditions for Seebeck value of inhomogeneity and validated with standard calibration using the liquid bath. This study has been considered successfully implemented that performs on IoT platforms and was adaptively ready to monitor thermocouple inhomogeneity equipment.